METHODS OF SOLVING NON-STANDARD PROBLEMS INVOLVING MATRIX AND DETERMINANTS FOR THE STUDENT SCIENCE OLYMPIAD - Hamdambek Nuraddinovich Kuromboyev (Galaxy International Interdisciplinary Research Journal, 2022)
In this article, convenient ways to solve some non-standard problems found in Science Olympiad problems for students of non-mathematical bachelor’s degree in Higher Mathematics are presented.